The study of thermodynamics properties of substances in the phase transition liquid-vapor - B. A. Arutionov; A. B. Arutionov (Тонкие химические технологии)
A study of the phase transition liquid-vapor allowed finding reasonable thermodynamic scales for the construction of generalized dependence of various properties.